Survey on the attitudes of school community members regarding the role of the language(s) of schooling in the integration process of pupils with an immigrant background in Slovenia - Čok, Tina (CEPS journal, 2024)
In terms of integration policy, Slovenia is considered a country that pro-motes the integration of children with an immigrant background into schools as quickly as possible. However fast the integration process may be, languages always play a key role in the education of pupils with an immigrant background and teachers need to adapt to their different lan-guage needs and literacy levels. Furthermore, it is important that teachers use teaching methods that promote pupils’ linguistic development in their mother tongue as well. In this paper, we present the results of research on the role of languages of schooling in the success of all pupils in Slovenian primary education institutions, with a focus on those with an immigrant background. To achieve this goal, we conducted an anonymous survey (n = 78) among teachers and support staff and interviewed principals from nine Slovenian primary schools. The main aim of the survey and inter-views was to investigate the status and understanding of the role of the languages of schooling in the context of the newly proposed cognitive-in-clusive language didactics based on collaborative learning. The study found that while school staff recognise the importance of multilingual education and linguistic integration, there are significant gaps in training and sup-port mechanisms for teachers. Although schools generally support the use of multiple languages, there is a lack of cross-language awareness and vis-ible promotion of multilingualism in the school environment. The findings of the study suggest the need to introduce comprehensive, standardised training and support for teachers that focuses on improving cross-language awareness and inclusive educational practices, which can ultimately lead to better integration outcomes for immigrant pupils and enrichment of the educational environment for all members of the community.
Keywords: cognitive-inclusive didactics; collaborative learning; Didaktika; Jeziki; jezikovna integracija; kognitivno-inkluzivna didaktika; language(s) of schooling; linguistic integration; sodelovalno učenje; učni jezik(i); Vrstniško poučevanje